Secondary Complete Cytoreduction in Recurrent Ovarian Cancer: Benefit of Optimal Patient Selection Using Scoring System. Issue 2 (1st February 2014) - Laas, Enora; Luyckx, Mathieu; De Cuypere, Marjolein; Selle, Frederic; Daraï, Emile; Querleu, Denis; Rouzier, Roman; Chéreau, Elisabeth
Abstract : Objective: Complete tumor cytoreduction seems to be beneficial for patients with recurrent epithelial ovarian cancer (REOC). The challenge is to identify patients eligible for such surgery. Several scores based on simple clinical parameters have attempted to predict resectability and help in patient selection for surgery in REOC. The aims of this study were to assess the performance of these models in an independent population and to evaluate the impact of complete resection. Materials and Methods: A total of 194 patients with REOC between January 2000 and December 2010 were included in 2 French centers. Two scores were used: the AGO DESKTOP OVAR trial score and a score from Tian et al. The performance (sensitivity, specificity, and predictive values) of these scores was evaluated in our population. Survival curves were constructed to evaluate the survival impact of surgery on recurrence. Results: Positive predictive values for complete resection were 80.6% and 74.0% for the DESKTOP trial score and the Tian score, respectively. The false-negative rate was high for both models (65.4% and 71.4%, respectively). We found a significantly higher survival in the patients with complete resection (59.4 vs 17.9 months, P < 0.01) even after adjustment for the confounding variables (hazard ratio [HR], 2.53; 95% confidence interval, 1.01–6.3; P = 0.04). Conclusions: In REOC, surgery seems to have a positive impact on survival, if complete surgery can be achieved. However, factors predicting complete resection are not yet clearly defined. Recurrence-free interval and initial resection seem to be the most relevant factors. Laparoscopic evaluation could help to clarify the indications for surgery.